2010
DOI: 10.1007/s11626-010-9362-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of enamel matrix protein expression in an ameloblast cell line co-cultured with a mesenchymal cell line in vitro

Abstract: Interactions between epithelium and mesenchyme are important for organ and tissue development. In this study, in order to mimic interactions between epithelium and mesenchyme during native tooth development, we constructed three-dimensional culture systems in vitro using a collagen membrane. Two types of collagen membrane-based in vitro culture systems were constructed in which dental epithelial and dental follicle cell lines were cultured. One co-culture method involved inoculation of one cell line into one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The HAT-7 cell line is an immortalized dental epithelial cell line derived from the cervical stem cell population of rat mandibular incisors. It can shift from the transient amplification stage to ameloblast lineage cells (26). SDC4 expression was downregulated by siRNA, which had no effect on the gene expression of SDC1, 2 or 3, the other three known members of the SDC family (27).…”
Section: Discussionmentioning
confidence: 95%
“…The HAT-7 cell line is an immortalized dental epithelial cell line derived from the cervical stem cell population of rat mandibular incisors. It can shift from the transient amplification stage to ameloblast lineage cells (26). SDC4 expression was downregulated by siRNA, which had no effect on the gene expression of SDC1, 2 or 3, the other three known members of the SDC family (27).…”
Section: Discussionmentioning
confidence: 95%
“…The reaction mixture was composed of 10 μL of SYBR Premix Ex Taq II (Takara), 10 pmol each of the forward and reverse primers, 2 μL of cDNA, and distilled water to a final volume of 20 μL. The thermocycling conditions were 95 °C for 30 s, followed by 40 cycles of 95 °C for 5 s and 60 °C for 34 s. Normalization of the data was performed using the housekeeping gene glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as an endogenous control in the same reaction as the gene of interest [49]. The primers used in this study were as follows: for GAPDH, forward primer 5′-CCCCCACCACACTGAATCTC-3′ and reverse primer 5′-GCCCCTCCCCTCTTCAAG-3′; for heme oxygenase 1 (HMOX-1), forward primer 5′-GGGTGATAGAAGAGGCCAAGA-3′ and reverse primer 5′-AGCTCCTGCAACTCCTCAAA-3′; for IL-6, forward primer 5′-TGAGTACAAAAGTCCTGA-3′ and reverse primer 5′-TCTGTGCCT GCAGCTTCGT-3′; for granulocyte-macrophage colony stimulating factor 2 (CSF-2), forward primer 5′-TCTCAGAAATGTTTGACCTCCA-3′ and reverse primer 5′-GCCCTTGAGC TTGGTGAG-3′.…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that ameloblastin expression in HAT-7 cells was induced by co-culture with BCPb8 cells by using the collagen membrane (Matsumoto et al 2011). We have constructed two co-culture models to investigate the interaction between two different dental cell lines, a rat HAT-7 cell line that originated from dental epithelia, and bovine BCPb8 cells, derived from cementoblast progenitor cells.…”
Section: Resultsmentioning
confidence: 99%
“…During tooth development, various growth factors, such as, fibroblast growth factor, transforming growth factor-β, and insulin-like growth factor (IGF), regulate cell proliferation and differentiation in a paracrine or autocrine fashion (review by Joseph et al 1996; Thesleff and Mikkola 2002; Thesleff 2003). To investigate the interaction between epithelial and mesenchymal cells, we previously constructed a three-dimensional culture system by using a collagen membrane, which induces the differentiation of epithelial cells (Matsumoto et al 2011). Our results suggest that soluble factors produced by mesenchymal cells contribute to the induction of epithelial cell differentiation.…”
Section: Introductionmentioning
confidence: 99%